APLIKASI UJIAN ONLINE COMPUTER ASSISTED TESTBERBASIS WEBSITE (STUDI KASUS SMPN 2 SELAJAMBE) - lathifah zulfa, neng sri; Ajeng Tresnawati (Universitas Islam Al-Ihya Kuningan, 2025)
During this time, technological developments are advancing rapidly, one of which is in the field of education. This research aims to create a website-based computer-assisted test online exam application to facilitate the exam at SMPN 2 Selajambe. This research uses a qualitative method. The qualitative method used includes two parts, including the data collection method and the software development method. The software development method used is the agile software development method. This research produced a website-based computer-assisted test online exam application that has access rights of 3 users, namely admins, teachers and students. After implementing the online exam application at SMPN 2 Selajambe on several students, students can do well in the exam. In addition, this application can minimize cheating when taking exams, because this application is equipped with a violation feature if students open other platforms. Then when implementing to several teachers, teachers can manage student usernames and passwords so that students cannot manipulate their identities. In addition, teachers can also manage questions with additional video and audio features to increase the attraction for students to take the exam.